The Bill of Rights : a bicentennial assessment - Bryner, Gary C., 1951-2010; Sorensen, A. Don (Alma Don), 1935- (Brigham Young University, 1993)
"The Bill of Rights: A Bicentennial Assessment is a companion volume to the three-volume series commemorating the Bicentennial of the United States Constitution. It explores rights in America by re-examining their roots, assessing their effectiveness, and considering their future." "Competing conceptions of rights are central to many of the most contentious public issues in the United States, such as free speech and the limits of public expression; affirmative action and the protection of minorities against discrimination; the role of religion and prayer in public schools and other public forums; capital punishment, searches and seizures, and issues affecting rights of the accused; and a host of concerns that have been characterized as personal rights of privacy - abortion, sexual preference, nontraditional forms of human reproduction, and withdrawal from life-sustaining medical technologies." "There is little agreement over what role rights should play in addressing these and other pressing contemporary issues. From one view, rights are a politically powerful way to expand government protection for certain interests. Critics, however, fear that an expansion of rights threatens traditional ones. The process of defining, interpreting, and extending rights is therefore almost as controversial as the substantive issues themselves." "Several questions provide the overall agenda for the essays in this book: What rights do people have? How are they determined? How do they shape and define the powers of government? What particular challenges does the protection of minority rights pose? How are rights secured? And, finally, what is the future of rights?" "By celebrating and assessing the Bill of Rights, we seek to engage in a free and open discussion of how well they have accomplished their purpose of securing basic individual liberties over the past two hundred years and how well suited they are to protect our rights in the future. We hope to learn from the example of the Framers of the Constitution in encouraging an examination of fundamental principles, studying the lessons of history, and looking toward the future."--Jacket